PENGELOLAAN KEUANGAN BISNIS ONLINE MENGGUNAKAN TELEPON PINTAR - Maulana, Sahdan; Fitrianingrum, Ayu; Damara, Abieza Satya; Quinta, Enno Astri; Sari, Evie Puspita; Hariputra, Kartiko; Mu’arief, M. Ilham; Zuti, Utari Ayuningrum; Raharjo, Taufik (LPPM Universitas Pamulang, 2020)
The object of this community service is SME Dpp.bookstore. The purpose of this community service activity is to raise awareness of the importance of accounting for and equip skills in financial management or accounting with the Android-based